Adolescent mental health services in West Africa: a comparative analysis of Burkina Faso, Ghana, and Niger - Michel Adurayi Amenah; Nassirou Ibrahim; Ludovic Deo Gracias Tapsoba; Jacob Novignon; Ama Pokuaa Fenny; Irene A. Agyepong; Roxane Borges da Silva; Tim Ensor (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Background Adolescent mental health (AMH) is a critical issue worldwide, particularly in West Africa, where it is intensified by socio-economic, cultural, and security challenges. Insecurity and the presence of mining sites expose adolescents to hazardous environments, substance abuse, and adulterated alcohol, further aggravating their mental health. Despite these severe issues, research on AMH in this region remains limited. This study aims to analyze the provision of AMH services in Burkina Faso, Ghana, and Niger, highlighting the unique challenges these countries face within the broader West African healthcare context. Methods The study adopted a multi-stage, stratified sampling design to collect data from primary healthcare centers (PHCs) in the three countries. Using STATA.17, Descriptive analysis was conducted on the data related to availability of AMH services, types of mental health disorders treated, resources available, and OPD attendance rates. The analysis also incorporated factors such as the rural-urban divide and the presence of national guidelines for AMH services. Results The findings reveal a significant shortfall in the provision of AMH services across the region, with less than 30% of PHCs across all the countries offering these services. The study also highlights a pronounced rural-urban disparity in AMH service availability, a general absence of national guidelines for AMH care, and low OPD attendance rates. Conclusion The study highlights the urgent need for comprehensive policy reform and targeted interventions to enhance AMH services in West Africa. Key policy reforms should include the development and implementation of national guidelines for AMH care and integration of AMH services into primary healthcare. Additionally, efforts should focus on capacity building through the training of mental health professionals, increasing public awareness to reduce stigma, and ensuring equitable resource allocation across rural and urban areas. Improving AMH care is essential not only for the well-being of adolescents but also for driving broader socio-economic development in the region.